Location of Distributed Generation by the Perspective of Sustainable Development - Cardoso de Lima, G. S.; Leite, P. T.; Canesso, B. C.; Zambon, K. L. [UNESP]; IEEE (Ieee, 2015)
This paper aims to propose a methodology to assist in the installation location of distributed generation units in order to promote the development aspects, which are aggregated variable aspects of economic, social and environmental, for decision making. To achieve the proposed objective, we sought the integration of Geographic Information Systems (GIS) and multi-criteria analysis methodologies, as a weighted linear combination and ordered weighted average. The evaluation was applied for locating wind turbines in the municipalities of Sao Paulo, Brazil, where the criteria analyzed were the grid connectivity, availability of energy resources, environmental protection areas and coverage of basic needs of electrification.
Keywords: Power generation; Renewable energy sources; Sustainable development